WhatsApp as a strategy to socialise funeral products during the Covid-19 pandemic - Prihatiningsih, Witanti; Maliki, Musa; Ayuningtyas, Fitria; Intyaswati, Drina; Maella, Nurannafi Farni Syam (Jurnal Studi Komunikasi, 2022)
The Covid-19 pandemic has forced many people to stay at home. People in Indonesia are encouraged to work from home (WFH) from 2020 until 2022. The WFH has significantly impacted the economy, especially among field workers. The MA cannot promote its product and services during this time. Therefore, the sales are decreasing. This study describes how the MA uses WhatsApp to socialise their product and services to seek potential customers amid the pandemic. This research involved descriptive qualitative methods, with five MAs as respondents. This study showed that the MAs maximised WhatsApp in socialising funeral products to customers during the pandemic. MAs used WhatsApp features such as "Profile Picture" and "Status" to attract people by keeping their contact numbers. The funeral product details were later socialised in texts, photos, and videos funeral prices will never be mentioned by the MA unless potential customers are asking about it.